2010
DOI: 10.1143/apex.3.101003
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Ideal Current–Voltage Characteristics of Schottky Barrier Diodes Formed on Hydride-Vapor-Phase-Epitaxy-Grown GaN Free-Standing Substrates

Abstract: The current–voltage characteristics of Schottky barrier diodes formed on GaN(0001) free-standing substrates with net donor concentrations of 7.6×1015–1.4×1017 cm-3 are discussed. The substrates were grown by hydride vapor phase epitaxy. Ni Schottky contacts were directly formed on chemical–mechanical-polished Ga-polar faces of the substrates. Nearly ideal characteristics for both directions were obtained. The ideality factors for forward characteristics are 1.02–1.05, very close to unity. The reverse character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 22 publications
6
95
0
1
Order By: Relevance
“…However, the performance of GaN vertical devices is inferior to SiC and Si power devices as yet though the material potential of GaN is very high. Recent diode researches have revealed that the quality of recent GaN substrates is enough to apply to high voltage devices [18][19][20]. We have confirmed that edge and mix (edge + screw) dislocations included in the GaN substrate do not induce leakage current though the dislocation density was ~ 10 6 cm -2 [21].…”
Section: Lower Arm 500μmsupporting
confidence: 54%
“…However, the performance of GaN vertical devices is inferior to SiC and Si power devices as yet though the material potential of GaN is very high. Recent diode researches have revealed that the quality of recent GaN substrates is enough to apply to high voltage devices [18][19][20]. We have confirmed that edge and mix (edge + screw) dislocations included in the GaN substrate do not induce leakage current though the dislocation density was ~ 10 6 cm -2 [21].…”
Section: Lower Arm 500μmsupporting
confidence: 54%
“…3 In addition, the Schottky diodes on the GaN layers with low dislocation densities showed nearly ideal I-V characteristics according to a simple thermionic field emission model. 4 These results indicate highly improved crystalline quality of the current n-GaN epitaxial layers grown on the GaN substrates.…”
Section: à2mentioning
confidence: 86%
“…23 Then the values of the depletion region width below the Ni/ Au electrodes were about 4.4 lm and 0.3 lm for sample 1 and sample 0, respectively. In addition, due to the existence of surface states, there is surface band bending and surface depletion region in GaN which is not covered by metal electrodes.…”
mentioning
confidence: 90%